Sociological Views on Sport Practices in Sports Facilities of Brazzaville, Congo - Litoto Pambou, Lucien; Bayette, Jean Bruno; Elenga, Hygin Bellarmin; Leyinda, Pascal Alain; Loufoua-Lemay, Emile Didier; Massamba, Alphonse (Advances in Social Sciences Research Journal, 2023)
The aim of this study was to characterize the population frequenting Brazzaville’s sports facilities and spaces, and to explore the universe of physical activities practiced and their modalities. A total of 5,492 users took part in the study, which was carried out in four districts of Brazzaville covering about half the city’s surface area. Data were collected using a questionnaire based on Chifflet’s work on the use of sports facilities in France. The results showed that the spatial distribution of the facilities did not provide an adequate sports offer for users, despite the population’s enthusiasm for sports and the demand from a young, active clientele.